A Labour Force for the Consumer Century: Commodification in Canada's Largest Department Stores, 1890 to 1940 - Belisle, Donica (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2006)
Abstract Between 1890 and 1940 Canada’s three largest department stores — Eaton’s, Simpson’s, and the Hudson’s Bay Company — developed a multifacted system of employee commodification. Not only did they encourage their employees to become avid consumers, so did they market their employees’ activities, interests, and bodies. They undertook these commodifying gestures in an attempt to extract value from their workforces. Investigating the rise and operation of commodification at these major retailers, this paper offers new insights into corporate management systems, demonstrates that commodification had negative consequences for employees, and provides fresh perspectives on 20th-century consumer capitalism.